Optimization of Business Sustainability Based on Green Human Resources Management in Jepara Furniture SMEs - Arifin, Noor; Mohammad, Gunawan; Imron, Much; Palupi, Majang; Alimin, Noor Azreen (Jurnal Manajemen Bisnis, 2025)
Research aims: This study explores the effect of Green Human Resources Management (GHRM) practices on Business Sustainability through Green Work Engagement and Green Innovative Work Behavior in the context of furniture SMEs in Jepara. The research is underpinned by the AMO concept (Ability, Motivation, Opportunity) theory, with the objective of promoting pro-environmental business commitments and enhancing sustainable performance.Design/Methodology/Approach: This descriptive quantitative research employs explanatory analysis using SEM-PLS (Structural Equation Modeling-Partial Least Squares). Data were collected through purposive sampling from 116 furniture SMEs in Jepara Regency. The factors were assessed on a Likert scale, and statistical analysis was performed to evaluate the proposed relationships.Research findings: The findings reveal that GHRM practices significantly positively affect Green Innovative Work Behavior and Green Work Engagement. Furthermore, Green Innovative Work Behavior and Engagement significantly influence Business Sustainability. However, GHRM practices alone do not directly impact business sustainability; they demonstrate a significant indirect effect when moderated by Green Innovative Work Behavior and Engagement.Theoretical Contribution/Originality: This study extends the application of AMO theory by demonstrating how GHRM practices contribute indirectly to business sustainability through green behavioral mechanisms. It highlights the critical role of employee engagement and innovation in achieving sustainability goals within environmentally focused SMEs.Practitioners/Policy Implications: The results underline the significance of adopting GHRM practices, such as eco-friendly training and recruitment, to foster employee engagement and innovative behaviors. Policymakers and practitioners in SMEs should focus on strategies that align organizational goals with environmental sustainability to gain competitive advantages in the market.Research Limitations/Implications: This study's limitation pertains to SMEs in Jepara Regency, perhaps constraining the generalizability of the findings. Future research may investigate the relevance of these findings in different areas or industries to deepen the comprehension of GHRM's wider ramifications.